2018
DOI: 10.3390/ijms19103149
|View full text |Cite
|
Sign up to set email alerts
|

Zerumbone, a Tropical Ginger Sesquiterpene of Zingiber officinale Roscoe, Attenuates α-MSH-Induced Melanogenesis in B16F10 Cells

Abstract: Zerumbone (ZER), an active constituent of the Zingiberaceae family, has been shown to exhibit several biological activities, such as anti-inflammatory, anti-allergic, anti-microbial, and anti-cancer; however, it has not been studied for anti-melanogenic properties. In the present study, we demonstrate that ZER and Zingiber officinale (ZO) extract significantly attenuate melanin accumulation in α-melanocyte-stimulating hormone (α-MSH)-stimulated mouse melanogenic B16F10 cells. Further, to elucidate the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…The used melanoma models are also listed in the Table. Zerumbone B16-F10 [226] where not indicated, EO active components were not available from the cited articles. When referred to in vivo studies, the murine strain used is indicated in brackets.…”
Section: 7 Sensitization Of Antitumor Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The used melanoma models are also listed in the Table. Zerumbone B16-F10 [226] where not indicated, EO active components were not available from the cited articles. When referred to in vivo studies, the murine strain used is indicated in brackets.…”
Section: 7 Sensitization Of Antitumor Agentsmentioning
confidence: 99%
“…Regarding the antimelanogenic effect of EO components, the study of Lin JH's group reported the ability of zerumbrone to decrease melanin accumulation in B16-F10 cells, and to suppress the expression of MITF and its target genes, TYRP1 and TYRP2, after MSH stimulation with a mechanism involving ERK1/2, but not the PKA-CREB signaling pathway [226]. Antimelanogenic activity in the same melanoma model through ubiquitination and proteasomal degradation of MITF, in a ROS/ERK-dependent way, was also reported for phytol [223].…”
Section: Antimelanogenic Activitymentioning
confidence: 99%
“…Intracellular tyrosinase activity was determined according to a modified version of a previously described method [26]. Briefly, B16F10 cells were harvested with lysis buffer containing a proteinase inhibitor, and then 20 μl of lysate and 80 μl of 2 mM l-DOPA were added to each well of a 96-well plate and incubated for 2 h at 37 °C.…”
Section: Intracellular Tyrosinase Activity Assaymentioning
confidence: 99%
“…In addition, a variety of other natural extracts for increasing pigmentation have been studied, including Cornus officinalis methanol extract [7], Ardisia crenata extract [8], and Zingiber cassumunar Roxb. [9]. Similarly, many other studies have used organic materials to stimulate pigmentation.…”
Section: Introductionmentioning
confidence: 99%